Role of Gut Microbiota in Immune System Regulation: Gut Microbiota in Immune System Regulation - Attiq, Talia; Farrukh Alavi, Amina; Khan, Shahzaib; Najam, Fatima; Saleem, Maleeha; Hassan, Irum; Ali, Roomana; Khaskheli, Hameer Khan; Sardar, Samran; Farooq, Fiza (Pakistan Journal of Health Sciences, 2024)
The human gut is a densely populated organ system that bears hundreds of microbial species, including bacteria, viruses, and various protozoans. The gut microbiome expresses enormous functional diversity based on microbial community collection. However, this has remained unexplored for a long time, but in the recent past various researches have revealed its immense significance in host metabolism and immunity. Gut microbiota metabolize undigested substances and release various metabolites in response to microbial metabolism that have a significant effect on the immune system. The balance and stability of the immune system within the body are achieved and maintained through the complex interaction between the gut microbiota and the host mucosal immune system. Upon loss of control by the immune system, dysbiosis occurs, the modulation of the microbial community, which leads to different disorders, including inflammatory bowel disease and colorectal cancer. Moreover, dysbiosis is also associated with various autoimmune diseases such as rheumatoid arthritis, diabetes mellitus, and multiple sclerosis. Despite its intricate mechanism in autoimmune diseases, various therapeutic strategies are utilized to treat chronic diseases, including prebiotics treatment, personalized probiotics therapy, fecal microbiome transplantation, and narrow-spectrum antibiotic treatment. This review discusses the interaction of gut microbiome with the immune system, how this association becomes dysregulated, its various outcomes in the form of autoimmune diseases, and therapeutic interventions to cope with it.